The Ponseti Method for the Treatment of Clubfeet Associated With Amniotic Band Syndrome: A Single Institution 20-Year Experience. Issue 5 (12th May 2021) - Esparza, Melissa; Tran, Elaine; Richards, Benjamin Stephens; Jo, Chan-hee; Shivers, Claire; Karacz, Chelsea; Polk, Jordan; Riccio, Anthony I.
Abstract : Background: Amniotic band syndrome (ABS) is a congenital disorder resulting in fibrous bands that can cause limb anomalies, amputations, and deformities. Clubfoot has been reported in up to 50% of patients with ABS. The purpose of this study is to compare treatment characteristics and outcomes of clubfoot patients with ABS to those with idiopathic clubfoot treated with the Ponseti method. Methods: An Institution Review Board (IRB) approved retrospective review of prospectively gathered data was performed at a single pediatric hospital over a 20-year period. Patients with either idiopathic clubfeet or clubfeet associated with concomitant ABS who were <1 year of age and treated by the Ponseti method were included. Initial Dimeglio score, number of casts, need for heel cord tenotomy, recurrence, and need for further surgery were recorded. Outcomes were classified as "good" (plantigrade foot±heel cord tenotomy), "fair" (need for a limited procedure), or "poor" (need for a full posteromedial release). Results: Forty-three clubfeet in 32 patients with ABS, and 320 idiopathic clubfeet in 215 patients were identified. Average age at last follow up was not different between ABS and idiopathic cohorts (7.4 vs. 5.2 y, P =0.233). Average Dimeglio score was lower in the ABS cohort (12.3 vs. 13.7, P =0.006). Recurrence rate was significantly higher in the ABS (62.8%) compared with idiopathic cohort (37.2%) ( P =0.001). Clinical outcomes were significantly better in the idiopathic cohort (69.4% "good", 26.9% "fair", 3.8% "poor") compared with the ABS cohort (41.9% "good", 34.9% "fair", and 23.3% "poor") ( P <0.001). Within the ABS cohort, no significant differences in clinical outcomes were found based upon location, severity, or presence of an ipsilateral lower extremity band. Conclusion: Clubfeet associated with ABS have higher rates of recurrence, a greater need for later surgery, and worse clinical outcomes than idiopathic clubfeet. This information may prove helpful in counseling parents of infants with ABS associated clubfeet. Level of Evidence: Level III.